2019
DOI: 10.1049/el.2018.7228
|View full text |Cite
|
Sign up to set email alerts
|

Secure communication in multigroup multicasting cell‐free massive MIMO networks with active spoofing attack

Abstract: The authors investigate the secure communication in multigroup multicasting cell-free massive MIMO systems in the presence of an active pilot spoofing attack. With the imperfect estimated local channels at access points, a distributed conjugate beamforming with normalised power constraint policy is exploited for downlink multicasting transmission. Closed-form expressions for the per-user achievable rate and information leakage to eavesdropper are derived, respectively. Numerical results are presented to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
(20 reference statements)
1
12
0
Order By: Relevance
“…Since cell‐free massive MIMO systems permit the APs and users to operate with low transmission power, the jamming attack in cell‐free massive MIMO systems should be taken seriously. However, there are only a few works focusing on the jamming aspects in cell‐free massive MIMO systems 13‐15 . In particular, Zhang et al 13 investigated the impact of pilot spoofing attack on a downlink multi‐group multi‐casting cell‐free massive MIMO system and demonstrated that the considered attack results in a significant secrecy rate reduction.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since cell‐free massive MIMO systems permit the APs and users to operate with low transmission power, the jamming attack in cell‐free massive MIMO systems should be taken seriously. However, there are only a few works focusing on the jamming aspects in cell‐free massive MIMO systems 13‐15 . In particular, Zhang et al 13 investigated the impact of pilot spoofing attack on a downlink multi‐group multi‐casting cell‐free massive MIMO system and demonstrated that the considered attack results in a significant secrecy rate reduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only a few works focusing on the jamming aspects in cell‐free massive MIMO systems 13‐15 . In particular, Zhang et al 13 investigated the impact of pilot spoofing attack on a downlink multi‐group multi‐casting cell‐free massive MIMO system and demonstrated that the considered attack results in a significant secrecy rate reduction. In addition, Hoang et al 14 proposed a downlink secrecy rate maximization power control algorithm to compensate for the rate loss caused by pilot spoofing attack.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors in [20] investigated the secure transmission of the Cell-Free massive MIMO system under a pilot spoofing attack, which also provided optimal power allocation schemes to maximize the achievable data rate or achievable secrecy rate. Moreover, authors in [21] firstly studied the security aspect of multigroup multicasting Cell-Free massive MIMO systems and provided the closed-form expressions for the achievable secrecy rate. However, only uplink training was considered in this paper.…”
Section: Introductionmentioning
confidence: 99%